Exploring ICT-supported Formal Women Business Networks (eFWBNs) the case of Kenya and South Africa - Ajumobi, Deborah O (Department of Information Systems, 2018)
The primary purpose of this study was to examine and understand the nature of Information and communication technology (ICT) supported formal women business networks (eFWBNs) and their contribution to the development of women entrepreneurs. For over a decade, studies on women’s entrepreneurship, particularly those in sub-Saharan Africa, have reiterated the importance of, and need for, women’s involvement in formal women business networks (FWBNs). In this study, FWBNs are defined as networks that have women entrepreneurs as key actors and are often affiliated with consultants, business practitioners, and government. FWBNs provide benefits and access to useful resources that are not easily accessible to women entrepreneurs due to several constraints. FWBNs have been found to be slow to leverage ICTs to facilitate and enhance their activities even in the era of globalisation. While FWBNs exist in sub-Saharan Africa, there is a dearth of research on their characteristics, structure and operation. Particularly within the information systems field, there is paucity of recearch around the integration and use of ICTs in WBNs. Thus, there is limited guidance on what makes a FWBN achieve its objectives and how these networks may leverage technology to enhance and facilitate their operations and activities. For these reasons, this study sought to shed light on the nature of eFWBNs and their use of ICTs. To achieve this objective, multidisciplinary theories were reviewed and an integrative theoretical framework developed. This revealed that an eFWBN is a configuration of distinct but inter-related elements – actors, relationships, resources, governance, external support and ICTs – which interplay to provide contributions and benefits to women entrepreneurs. This thesis proposed that the stronger the coherence among the core elements of the eFWBN, and the operating and support mechanisms, the greater will be their contribution and benefits. This proposition was tested in an empirical study involving three network cases in Kenya and South Africa, using mixed methods. The qualitative data was analysed using thematic analysis, and converted to quantitative data using the quantitisation technique. The quantitised data and the data collected using quantitative methods were combined to test the model using cluster analysis. The cluster analysis resulted in three clusters representing the three eFWBNs cases in this study. The findings revealed that the Kenyan networks had achieved coherence amongst the elements of the network and as such attained good outcomes. However, the South African network did not report good outcomes, suggesting they had not attained coherence amongst the element in the network. The findings also provided results contrary to the observations in literature about the use of ICTs in eFWBNs. In this study, not only ICTs were highly leveraged at the network-level and were an integral part to the strategy, the existence and operation of the network. This research makes significant contribution to knowledge by providing insight and understanding into an under-researched area (eFWBNs). The key theoretical contribution of this study is the integrative theoretical framework that overcomes the limitations of earlier theories used to study networks. It integrates various theories into a framework that identifies and explains more comprehensively the various aspects and operations of eFWBNs. It also advances the configurational theory as an effective approach to measuring complex relationships. This study also makes significant methodological contributions. There is currently a dearth of knowledge on how to fully integrate both qualitative and quantitative data in mixed methods research. Thus, by adopting the quantitisation technique, this study provides knowledge on how to convert qualitative data to quantitative data to achieve synthesis of both methods in a single study. Also, the adoption of realism as a philosophical stance helped to overcome the challenges of mixing methods and paradigms in one research project. The findings of this study also have practical implications. The findings showed that at the membership level, women entrepreneurs need to apply more agency in establishing relationships and translate the acquired resources within the network into benefits for their businesses. At the network-level, the evidence revealed that leaders of eFWBNs need to ensure they balance the needs of their members in order to carry the members along and preventing them from feeling excluded. The findings also asserted the importance of developmental, private and public organisations to eFWBNs. Lastly, government and practitioners can draw from the understanding provided of eFWBNs, to create and establish policies that can aid women entrepreneurs’ successes and growth. The theoretical, practical and methodological contributions are further discussed in this thesis. The study concludes with a discussion on the limitations of the study and recommendations for future research.